Determination of progesterone contents in female silkworm (Bombyx mori) moth by radioimmunoassay - GU Yan-yan; HE Wei-qiang; SHI Lian-gen (浙江大学学报. 农业与生命科学版)
Method for determining the contents of progesterone in female silkworm (Bombyx mori) moth was studied. The progesterone could be efficiently extracted out from the female silkworm moth according to following conditions: grinding the female moth powder and sifting through 80 item, using 0.1 mol·L-1 HCl as dispose solvent, ether as extract solvent, and extracting for three times. Using 90 g·L-1 bovine serum albumin Tris buffer as determination solvent, the contents of progesterone in female silkworm moth could be exactly and stably measured by radioimmunoassay. This method could be applied in determination of progesterone in female silkworm moth powder and its products for large numbers of samples.